Two-Tier Fallacy Theory: A New Approach to Assessing Argument Quality - Hinton, Martin; Wagemans, Jean H. M. (Informal Logic, 2025)
Conceptions of fallacies suggested by philosophers vary significantly. Often these contributions are little more than lists, only sometimes approaching a fully-developed theory of fallacy. Where there is a clear understanding of what is meant by the term fallacy, the problem of how to identify them in discourse remains, often leading to a conflation of descriptive and evaluative analyses. We present a two-tier procedure that strictly distinguishes the descriptive and normative dimensions of identifying fallacies. The combination of the descriptive Argument Type Identification Procedure (ATIP), which enables the characterization of an argument in terms of the Periodic Table of Arguments (PTA), and the evaluative Comprehensive Assessment Procedure for Natural Argumentation (CAPNA), provides a basis for systematic, repeatable, and explainable argument acceptability judgements. We explain how this two-tier procedure overcomes some of the difficulties of fallacy identification and categorization and list several other advantages that a procedural approach to fallacies brings.